Performances trans: a arte de existir enquanto subversões - Boaro, Jhully Cristine Ananias (Universidade Federal de São Carlos, 2024)
This study explored the life trajectories of trans digital artists, through art, as forms of existence and reiterations not prescribed by binary gender norms, with the theoretical backing of the theory of subjection, under a Butlerian reading. The research, submitted to and approved by the UFSCar Human Research Ethics Committee (CAAE No. 58532822.0.0000.5504), was qualitative in nature, exploratory in nature and cross-sectional in design, through two semi-structured interviews, in remote mode, with four trans digital artists, in which life experiences were explored, as well as contact with the Binary Gender Norms, as well as experiences as a trans person and artist and relationships with primary and secondary figures of affection. The data was transcribed in full using Reshape software, using thematic analysis and semantic cut-outs, according to Bardin. Three categories were established using deductive and inductive methods: Binary Gender Norms, Performativity and Art. Contact with the norms proved to be a source of sadness, anguish and violence.Performativity, elaborated and updated through different artistic practices and the establishment of bonds with figures of affection. Art, a way of conquering a space in the world, in the masculine and feminine, building representativeness and acceptance, promoting identification and support, escaping from reality, carrying out aesthetic experiments, obtaining emotional relief and building hope and expectations for the future. Art has therefore shown itself to be a way of Performing a transversal existence, which is re-inaugurated through making art and making oneself art.
Trans performances: the art of existing as subversions
Keywords: Identidade de gênero; Binarismo de gênero; Transexualidade; Artes; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO